Revealing of the transition from n- to p-type conduction of InN:Mg by photoconductivity effect measurement - Guo, L.; Wang, X. Q.; Zheng, X. T.; Yang, X. L.; Xu, F. J.; Tang, N.; Lu, L. W.; Ge, W. K.; Shen, B.; Dmowski, L. H.; Suski, T. (Scientific reports, 2014)
We report evidence of the transition from n- to p-type conduction of InN with increasing Mg dopant concentration by using photoconductivity (PC) measurement at room temperature. This transition is depicted as a conversion from negative to positive PC under above-bandgap optical excitation. The n- to p-type transition in InN:Mg is further confirmed by thermopower measurements. PC detection method is a bulk effect since the optical absorption of the surface electron accumulation is negligibly low due to its rather small thickness and thus shows advantage to detect p-type conduction. This technique is certainly helpful to study p-type doping of InN, which is still a subject of discussions.